Bilateral lesions of CA1 and CA2 fields of the hippocampus are sufficient to cause a severe amnesic syndrome in humans. Issue 1 (July 1995) - Kartsounis, L D; Rudge, P; Stevens, J M
Abstract : A patient is reported in whom a classic amnesic syndrome developed as a result of repeated episodes of cerebral ischaemia, accompanied by seizures. The amnesia was very severe for both old and newly acquired memories and the critical lesions defined by MRI were circumscribed areas confined to CA1 and CA2 fields of both hippocampi.